DETEKSI DINI PERILAKU ANTISOSIAL AKIBAT PENGGUNAAN GADGET PADA REMAJA - Putri Putri; Inaya Mardhatila; Abelia Aisya Putri; Risma Anita Puriani; Rizki Novirson (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The development of technology, particularly the widespread use of gadgets, has brought significant changes to adolescent interactions. However, excessive use can potentially trigger antisocial behaviour. The purpose of this study was to detect antisocial behaviour in adolescents due to gadget use. The research method used was a literature study, which involved understanding and analysing 10 relevant articles. The results of the analysis indicate that interaction with gadgets can significantly influence antisocial behaviour. The main impact of uncontrolled gadget use is a decline in communication skills and healthy social interaction within the family and school environment. Additionally, exposure to negative online content, such as violence or hate speech, can exacerbate this condition and trigger antisocial behaviours like cyberbullying and unhealthy social comparisons. Prevention and supervision efforts involving parents, educators, and counsellors are necessary to detect and address the negative effects of gadget use. To that end, an educational approach that teaches wise use of technology and emphasises the importance of healthy social interaction is essential to reduce the impact of antisocial behaviour.